2018
DOI: 10.3892/etm.2018.6504
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor function of miR‑483‑3p on breast cancer via targeting of the cyclin E1 gene

Abstract: microRNA (miR)-483-3p has previously been demonstrated to be a tumor suppressor in many types of cancer cells, however it is unknown whether miR-483-3p is involved in the regulation of breast cancer. Therefore, the aim of the present study was to investigate the effects of miR-483-3p on breast cancer. The results demonstrated that the expression of miR-483-3p was decreased, especially in MCF-7 cells. The results of CCK-8 assay and cell cycle analysis demonstrated that miR-483-3p significantly reduced cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Overexpression of miR-647 promotes proliferation and migration of tumor cells by regulating expression levels of ANK2, FAK, MMP2, MMP12 and CD44 23. Previous studies have shown that miR-483-3p inhibits the progression of breast cancer by inhibiting CCNE1 expression 15. miR-483-3p reverses EMT and inhibits gefitinib resistance by directly targeting on integrin β3 through inhibiting downstream FAK/ERK pathway 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of miR-647 promotes proliferation and migration of tumor cells by regulating expression levels of ANK2, FAK, MMP2, MMP12 and CD44 23. Previous studies have shown that miR-483-3p inhibits the progression of breast cancer by inhibiting CCNE1 expression 15. miR-483-3p reverses EMT and inhibits gefitinib resistance by directly targeting on integrin β3 through inhibiting downstream FAK/ERK pathway 24.…”
Section: Discussionmentioning
confidence: 99%
“…circZNF609 shows an essential role in promoting myoblast proliferation 14. miR-483-3p inhibits the progression of breast cancer by inhibiting circCCNE1 expression 15. However, the roles of circZNF609 and miR-483-3p in GC have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…This result is similar to that in other studies of cell lines (30), and a recent study has suggested that the interaction between RNA-binding ubiquitin E3 ligase (MEX3C) and adaptor-related protein complex 2(AP-2) may contribute to the enrichment phenomenon (31). miR-483-5p has been identified as an anti-tumor miRNA in breast cancer by targeting histone deacetylase 8 or Cyclin E1, which suggested the effects of miR-483-3p on cell growth and apoptosis (32,33).…”
Section: Discussionmentioning
confidence: 93%
“…serves as an important target for tumor suppression/proliferation in BC [88]. For example, miRNAs, such as miR-497, miR-16, and miR-30c-2-3p, were reported to target and inhibit cell cycle regulator of G1-S transition, cyclin E1 leading to decreased cyclin E1 expression and suppression of proliferation by blocking BC cells from entering the S-phase of the cell cycle [89][90][91][92]. On the other hand, certain miRNAs, such as miR-483-3p, dysregulate the cell cycle transition by facilitating the formation of cyclin E1 and cyclin-dependent kinase CDK2 complex.…”
Section: Role Of Micrornas and Lncrna In Bcscsmentioning
confidence: 99%
“…On the other hand, certain miRNAs, such as miR-483-3p, dysregulate the cell cycle transition by facilitating the formation of cyclin E1 and cyclin-dependent kinase CDK2 complex. This leads to increased expression of cyclins, up-regulation of protein kinases and down-regulation of kinase inhibitors, thereby increasing BC cell viability and proliferation [92]. Similarly, overexpression of miR-1207-5p, has been associated with negative regulation of STAT2 expression and inactivation of cell cycle-dependent kinase inhibitors CDKN1A and CDKN1B thus promoting cell cycle progression in cancer cells [93].…”
Section: Role Of Micrornas and Lncrna In Bcscsmentioning
confidence: 99%